Visuospatial and Sensory Integration Tasks in Patients With Schizophrenia or Schizoaffective Disorder: Relationship to Body Mass Index and Smoking - Vanderhoof, Tyler S.; Gurvits, Tamara V.; Baker-Nolan, Julie E.; Borsook, David; Elman, Igor (Frontiers in Psychiatry, 2018)
Neurological soft signs (NSSs) are highly prevalent among patients with schizophrenia, but their pathophysiological significance remains unclear. The present study employed perceptual-motor and visuospatial processing tests that have not yet been attempted in this patient population. Patients with schizophrenia or schizoaffective disorder (n=42) and mentally healthy subjects (n=10) were administered Copy Figure Test, Detection and Recognition of an Object Test and Road Map Test. As compared to controls, schizophrenic and schizoaffective patients displayed significantly poorer ability to copy three-dimensional figures (namely, Necker- and hidden line elimination cubes) and to orient in space on a road-map test; group differences in copying two-dimensional figures and on objects’ recognition against a background noise were not apparent. In the schizophrenia/schizoaffective group, more mistakes on the hidden line elimination cube was associated with greater body mass index and greater severity of nicotine dependence measured via the Fagerstrom Test of Nicotine Dependence. The above findings replicate those of prior reports and extend them to the tasks that do not involve motivational and attentional confounds. Furthermore, the present data support the hypothesis that subtle cerebral cortical abnormalities detected with specific NSSs tests may be related to some aspects of metabolic and motivational function in patients with schizophrenia/schizoaffective disorder.